2021
DOI: 10.1186/s12935-021-02031-6
|View full text |Cite
|
Sign up to set email alerts
|

The underlying molecular mechanisms and prognostic factors of RNA binding protein in colorectal cancer: a study based on multiple online databases

Abstract: Background RNA binding protein (RBP) is an active factor involved in the occurrence and development of colorectal cancer (CRC). Therefore, the potential mechanism of RBP in CRC needs to be clarified by dry-lab analyses or wet-lab experiments. Methods The differential RBP gene obtained from the GEPIA 2 (Gene Expression Profiling Interactive Analysis 2) were performed functional enrichment analysis. Then, the alternative splicing (AS) events related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, BRCC3 was involved in BC cell proliferation and invasion by binding to TRAF1, thus influencing the activation of the NF-κB pathway [ 33 ]. In addition, the analysis from the TCGA database revealed that the mutated or aberrant expression of RBPs was closely related to the prognosis in patients with BC [ 34 ]. Our previous study revealed that RBM5, as an important RBP member, was downregulated in BC tissues and cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BRCC3 was involved in BC cell proliferation and invasion by binding to TRAF1, thus influencing the activation of the NF-κB pathway [ 33 ]. In addition, the analysis from the TCGA database revealed that the mutated or aberrant expression of RBPs was closely related to the prognosis in patients with BC [ 34 ]. Our previous study revealed that RBM5, as an important RBP member, was downregulated in BC tissues and cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The computed topmost occurrences using the STRING network show, that selected genes, e.g. CAPRIN2 or TM9SF2, are linked to the survival of colorectal cancer patients (He et al ., 2021; Clark et al ., 2018). The Spektral implementations also selected multiple genes related to colorectal cancer, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Time-dependent area under the curve (AUC) values were employed to compare the predictive accuracy of clinical predictors and the risk signature. Moreover, receiver operating characteristic (ROC) curves were used to compare the predictive ability of our signature with nine recently published prognostic signatures for CRC patients ( 20 28 ).…”
Section: Methodsmentioning
confidence: 99%